Re-narrating Europe in the Face of Populism: An Analysis of the Anti-immigration Discourse of Populist Party Leaders - (:unkn) unknown (SETA FOUNDATION, 2018)
Populist discourse is gaining more and more ground in Europe. As evidenced by the growing success of radical right wing parties, a ubiquitous right wing populism is haunting Europe. This populist discourse is a counter to the long-standing narratives of Europe. Clearly, with the alarming growth rate of the politics of fear and hatred, Europe is in contradiction with its own core values. It is the consistent and mainstream positioning of populist discourse, establishing itself in the name of protecting European identity. This argument is tested upon a case study of right wing populist party leaders' anti-immigration discourse from the Netherlands, Finland, Italy and Hungary; these narratives, which were once perceived as marginal, are currently occupying and dominating the national and European discourse.
Keywords: TRANSFORMATION